Painful Praise: Exploring the Public Proclamation of the Hymns of Revelation - Powery, Luke A. (Theology today, 2013)
In light of the present infatuation with praise music and prosperity preaching within some sectors of the church, this article attempts to complicate simplistic notions of praise and correct faulty conceptions of preaching. It does so by demonstrating the interrelationship of praise, preaching, and public life via an exploration of the hymns of Revelation 5. The public proclamation of these hymns reveals how praise, pain, and politics interface within a historical setting of Roman oppression. The article concludes with some implications of how this biblical “hymnic homiletic” can shape contemporary homiletics.